Profil Adaptabilitas Karier Siswa Kelas XII Automotif SMK PGRI 2 Palimanan Kabupaten Cirebon - Mukhyidin, Mukhyidin; Kiswanto, Andi (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
This study aims to measure the career adaptability of class XII Automotive students at SMK PGRI 2 Palimanan. The method used is quantitative descriptive, which aims to describe the current situation systematically and factually. Data were collected through career adaptability measurements on 79 students, which were divided into two categories: high and low. The results showed that 56 students (68.35%) had high career adaptability, while 23 students (31.65%) had low career adaptability. The highest score obtained by students was 72, and the lowest score was 45, with an average score of 57.64. This shows that the majority of students have good career adaptability. The increase in students' career adaptability is influenced by the cooperation between Guidance and Counseling (BK) teachers and the head of Career Guidance (BKK) in providing an understanding of career levels and motivation. Career guidance services at SMK PGRI 2 Palimanan help students to find and determine career fields that suit them. Thus, effective career guidance services can support students' career development.